2014
DOI: 10.1902/jop.2013.120705
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression in Gingival Tissues and Enhanced Bone Loss in Rats With Diabetes With Experimental Periodontitis

Abstract: The results of this study indicate that the role of DM in modulating bone breakdown related to periodontitis may involve an increased level of LBP and reduced levels of T-helper 2 cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Distinct animal experimentation protocols were used in the reviewed studies. The murine experimental models were used in 100% of the studies, from which the mouse model was the most frequently used animal model (76.2%) . In the studies using mice, 10 studies used the C57BL/6 strain, four studies used the BALB/c strain, and three studies did not specify the animal strain used .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Distinct animal experimentation protocols were used in the reviewed studies. The murine experimental models were used in 100% of the studies, from which the mouse model was the most frequently used animal model (76.2%) . In the studies using mice, 10 studies used the C57BL/6 strain, four studies used the BALB/c strain, and three studies did not specify the animal strain used .…”
Section: Resultsmentioning
confidence: 99%
“…From them, only eight studies reported the number of mice that were analysed (M = 22.6, SD = 8.30, total = 181 mice). In the studies using rats, three studies used the Wistar strain, two studies used the Sprague Dawley strain, and one study used the Zucker Diabetic Fat strain . All the studies reported the number of rats that were analysed (M = 33.3, SD = 7.76, total = 200 rats).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligature-induced periodontitis is a method to produce an animal model of periodontitis that is similar to clinical periodontitis since it results from plaque accumulation around the ligature23. Acute inflammation arises within 2 days post surgery, beginning around the cervical area and leading to a chronic inflammatory response, eventually ending in alveolar bone loss242526.…”
mentioning
confidence: 99%